SUSTAINABLE IN HIGHER EDUCATION OF WAGENINGEN UNIVERSITY & RESEARCH - Jusuf, A An Arief; Natalia, Irene (International Journal of Social Science, 2025)
Concerns about sustainability are shared by the corporate and academic groups. Organizations have become more knowledgeable about sustainability-related issues during the past 20 years, including what sustainability is, why it's significant, and how to manage and measure it. In 2016, the Dutch government unveiled its policy plan, “Circular Economy in the Netherlands by 2050.” The Netherlands will use fewer abiotic (mineral, metal, and fossil) resources thanks to the policy strategy. How Wageningen University & Research maintains its success in the field of higher education is the subject that this study seeks to address. We use a narrative approach. Wageningen University & Research's synergy has improved since the merger. It is the focus of many academic publications and has a substantial impact on environmental sustainability. Because we examine the story of Wageningen University & Research's success, a qualitative study is suited for this subject. The University of Indonesia, National Taiwan University, The Higher Education, the Government of the Netherlands, and particularly Wageningen University & Research are the primary targets of this study's narrative methodology, which focuses on published materials. The coordination of environmental, technological, and financial factors has been done by Wageningen University & Research. The importance of education in preserving the deteriorating environment that societal injustices have caused is growing. This study shows how Wageningen University & Research has expanded and continued to be successful. Environmental quality, sustainability, and governance have all been strategically managed.